2013
DOI: 10.7860/jcdr/2013/5630.2953
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Microwave Versus Conventional Tissue Processing: A Quantitative and Qualitative Analysis

Abstract: Background: Microwave irradiation has been tried as a replacement for the conventional tissue processing technique in histopathology laboratories for quite some time. Studies have shown that Domestic Microwave Tissue Processing (DMWTP) provides a faster delivery of the tissue sections with a morphology which is similar to that which is seen Conventional Tissue Processing (CTP). But many laboratories still confine the domestic microwave tissue processing method only to the handle selected specimens, for which u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The two methods did not show signiicant variation in terms of overall quality, consistent with the observations of numerous authors such as Rohr, Morales, Mathai, Devi, Babu. [1][2][3][4][5][6] Complete concordance of opinion with regard to quality of the two methods was seen in an average of 90.42% cases. Majority of tissue sections were of excellent quality (Score-4).…”
Section: Resultsmentioning
confidence: 82%
“…The two methods did not show signiicant variation in terms of overall quality, consistent with the observations of numerous authors such as Rohr, Morales, Mathai, Devi, Babu. [1][2][3][4][5][6] Complete concordance of opinion with regard to quality of the two methods was seen in an average of 90.42% cases. Majority of tissue sections were of excellent quality (Score-4).…”
Section: Resultsmentioning
confidence: 82%
“…Also, as observed in this study, it is recommended that the whole process should be monitored closely to avoid laboratory hazards that could be caused by the flammability of some reagents. Similarly, (Devi et al 2013), reported that plastics should be used for microwave irradiation, as metallic materials could cause the danger of explosion. About formalin fixation (Chaudhari, Chattopadhyay, and Dutta 2000), also recorded a satisfactory result of 80% cases.…”
Section: Discussionmentioning
confidence: 99%